A non Abelian effective model for ensembles of magnetic defects in 3D Yang–Mills theory - Fosco, Cesar Daniel (2013)
We construct a non Abelian model for SU(2) Yang–Mills theory in an Euclidean three-dimensional spacetime and study its different phases. The model contains a center vortex sector coupled to a dual effective field encoding information about how the vortices are paired in the ensemble. The possible phases in the parameter space are interpreted in terms of the proliferation of either closed center vortices or closed chains, where the endpoints of open vortices are attached in pairs to monopole-like defects.